Understanding mild asthma/episodic asthma in children - Robin Green (South African Family Practice)
Asthma may be intermittent or persistent and persistent asthma may be mild, moderate, or severe. Many factors influence asthma severity, both from day-to-day and from month-to-month. In individual patients, asthma severity may fluctuate because of many extrinsic (allergens, viral infections) and intrinsic (behavioural) factors. This article discusses the pathogenesis of episodic asthma and wheezing outlines a treatment approach for episodic asthma.